The bad seed (Food group series, , 1, 2019)
A naughty seed with a bad attitude, bad temper, and bad manners vows to change his life for the better, but his efforts are met with skepticism by his friends.

The cool bean (Food group series, , 1, 2019)
"Everyone knows the cool beans. They're sooooo cool. And then there's the uncool has-bean . . . Always on the sidelines, one bean unsuccessfully tries everything he can to fit in with the crowd--until one day the cool beans show him how it's done.

The good egg (Food group series, , 1, 2019)
When the other eggs in his carton behave badly, the good egg feels like he needs to be perfect.

The couch potato (Food group series, , 1, 2020)
"The Couch Potato has everything he needs within reach of his sunken couch cushion. But when the electricity goes out, Couch Potato is forced to peel himself away from the comforts of his living room and venture outside. When he does, he realizes fresh air and sunshine could be just the things he needs."--Provided by publisher.

The great eggscape! (Food group series, , 1, 2020)
The Great Eggscape is when the Good Egg and his pals escape their carton and drop into the store for a morning of fun, enjoyed by everybody. Well, almost everybody. Shel (an egg) isn't a huge fan of group activities, especially when he's made to be "It" for a game of hide-and-seek. Nevertheless, Shel doesn't want to let his friends down, so he reluctantly plays, anyway. But after a morning of hiding and seeking, somebody's still missing. Will the dozen eggs friends ever be reunited? Find out in this hilarious egg hunt adventure in the grocery store that reminds us to break out of our shells and help our friends in need!

The Bad Seed Presents: The Good, the Bad, and the Spooky (Food group series, , 1, 2021)
Based on the picture book sensation The Bad Seed, Jory John and Pete Oswald present: The Good, the Bad, and the Spooky! Halloween is the Bad Seed’s favorite holiday of the year. But what’s a seed to do when he can’t find a show-stopping costume for the big night? Postpone trick-or-treating for everyone, of course! Can he get a costume together in time? Or will this seed return to his baaaaaaaaad ways? Find out in this hilarious, charming, and thought-provoking continuation of Jory John and Pete Oswald’s series.

The smart cookie (Food group series, , 1, 2021)
"This cookie has never felt like a smart cookie no matter how hard she tries, especially in comparison to all the clever cupcakes and brilliant rolls in the bakery. Will a dash of creativity and a sprinkle of confidence be enough to help her learn that perfect scores and having all the answers aren't the only ingredients for intelligence?"--

The Bad Seed goes to the library (I Can Read Level 1, ,, 2022)
"The Bad Seed is in a good mood...for once. That's because there's a really cool book at the library available for checkout. The Bad Seed reads, and reads, until the book can't be read anymore. But suddenly, he gets bad news: The book must be returned to the library so another seed can enjoy it. Will the bad seed return to his baaaaaad ways and keep the book? Pick up this really cool book to find out! The Bad Seed Goes to the Library is a Level 1 I Can Read book, which means it's perfect for children learning to sound out words and sentences. Whether shared at home or in a classroom, the short sentences, familiar words, and simple concepts of Level One books support success for children eager to start reading on their own."-- Amazon.

The good egg and the talent show (I can read book, ,, 2022)
"The Good Egg discovers his true talent in this Level One I Can Read by the #1 New York Times bestselling duo Jory John and Pete Oswald! The talent show is today and the Good Egg is so excited. There's just one problem. He doesn't have an act! When the talent show starts, he accepts that he'll be just a regular ol' audience member. But when his friends need help on stage, the Good Egg steps up to help and discovers that being yourself and kindness deserve a standing ovation."-- Amazon.

The sour grape (Food group series, , 1, 2022)
"The Sour Grape holds grudges for every reason under the sun. Lime never returned a scarf they borrowed? Grudge! Orange never called back? Grudge! But when a friend holds a grudge against the Sour Grape without listening to an explanation, the Sour Grape realizes how unfair grudges can be. Could a bunch of forgiveness and compassion be enough to turn a sour grape sweet?"-- Amazon.

The Big Cheese (Food group series, , 1, 2023)
"The Big Cheese is the best at everything, and brags about it, too. When the annual Cheese-cathlon comes around, the Big Cheese is prepared to win, as always. But what happens when the quiet new kid, Wedge Wedgeman, comes out on top? Is a slice of humility all the Big Cheese needs to discover that some things are better than being the best?" --publisher's website